Rural realities in service provision for substance abuse: a qualitative study in uMkhanyakude district, KwaZulu-Natal, South Africa. Issue 3 (23rd May 2017) - Mpanza, DM; Govender, P
Abstract : Background: Substance abuse is recognised as a worldwide concern, contributing significantly to morbidity and mortality in South Africa. There is minimal research that has considered influences in mental health care service delivery in rural and disadvantaged communities in South Africa. Methods: A qualitative study with substance abuse service providers in uMkhanyakude rural district of KwaZulu-Natal was undertaken to gain insight into the experiences and challenges in service delivery. Focus groups and semi-structured interviews were conducted with various stakeholders ( n = 29) in the rural district. Results: The findings of the study suggest that service providers experience challenges in service delivery in this rural area. The effects of culture (amarula festival and ancestral worship) exacerbate the use of substances; the high rate of unemployment and poverty lead to the produce of home-brewed substances for sustainable living; a lack of resources poses threats to service delivery; the poor prioritisation of mental health care services and a lack of monitoring and evaluation of services in the district were highlighted. Conclusions: Despite this being a single district study, findings reflect the need for a district, provincial and national standard for substance abuse rehabilitation services in addition to the improvement of monitoring and evaluation for quality improvement. There is also a need to respond to the gaps that exist in after-care and community-based or decentralised substance abuse services that are essential in such areas, which are under-resourced despite the high prevalence of substance users.